Translatability of Metaphors in the Dubbing of Animation Songs from English into the Egyptian Dialect (Global Journal of Human-Social Science, 2020)
This research paper examined the ways how translators translated metaphors in the dubbing of animation songs and measured the degree of loss occurred in rendering metaphors from English into Arabic; these two languages are culturally and linguistically distinct languages. This study employed descriptive qualitative methods. The data used in this research were metaphors of songs from three animated musical movies: Beauty and the Beast, Tangled, and Pocahontas. This paper analyzed the translation of metaphors depending on the cognitive theory proposed by Mandelblit (1995). The results proved that even though translating metaphors in animation songs was a laborious process, they did not always cause a problem of untranslatability; on the contrary, translators can render metaphors from English onto Arabic without a significant loss in terms of meaning and sound patterns. Compensation in kind and compensation in place helped to achieve the translatability of metaphors in cartoon films' songs. The analysis of source and target metaphors revealed that there were three translation procedures used to translate metaphors in animation songs, namely: replacing the source metaphor with a target metaphor (substitution), translating the metaphor into sense (paraphrasing), and using literal translation.
Keywords: cognitive approach; metaphor; animation; alliteration; dubbing; compensation